Educational Mentoring for Indonesian Immigrant Children at Community Learning Centers in Sabah, Malaysia: Materials, Patterns, and Program Outcomes - Edhy Rustan; Abdul Rahim Karim; Abdul Hair Bin Beddu Asis (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: The presence of the Community Learning Centre (CLC) program in Sabah, Malaysia, has helped children of Indonesian migrant workers (TKI) access education. However, learning in the CLC program has not been optimal. Purpose of the Study: this study aims to maximise educational services for Indonesian immigrant children in Sabah, Malaysia. Methods: The mentoring program is implemented through a service-learning method integrated with the International Professional Training Education (PLP). The mentoring involves IAIN Palopo and the LPTK (Teaching Institution for Teachers and Teachers). The mentoring is carried out at CLC Holy Trinity Tawau, CLC AL Alaq Tawau, Pesantren As’adiyah Tawau, and CLC Cahaya Tagas. Results: The mentoring material can be divided into three: general and religious material for students, and learning management for teachers and principals. The mentoring pattern is adjusted to the needs. The impact of educational mentoring for immigrant children in Malaysia is very positive, so it needs to be continued on an ongoing basis. The mechanism for sending students to assist teachers at CLC Sabah needs to be strengthened with an MoU between the Consulate of the Republic of Indonesia and universities.